Effect of bleaching on sound enamel and with early artificial caries lesions using confocal laser microscopy - Berger, Sandrine Bittencourt; Pavan, Sabrina; Santos, Paulo Henrique dos [UNESP]; Giannini, Marcelo; Bedran-Russo, Ana Karina B. (FapUNIFESP (SciELO), 2012)
The aim of this study was to evaluate effect of bleaching agents on sound enamel (SE) and enamel with early artificial caries lesions (CL) using confocal laser scanning microscopy (CLSM). Eighty blocks (4 × 5 × 5 mm) of bovine enamel were used and half of them were submitted to a pH cycling model to induce CL. Eight experimental groups were obtained from the treatments and mineralization level of the enamel (SE or CL) (n=10). SE groups: G1 - unbleached (control); G2 - 4% hydrogen peroxide (4 HP); G3 - 4 HP containing 0.05% Ca (Ca); G4 - 7.5% hydrogen peroxide (7.5 HP) containing amorphous calcium phosphate (ACP). CL groups: G5 - unbleached; G6 - 4 HP; G7 - 4 HP containing Ca; G8 - 7.5 HP ACP. G2, G3, G6, G7 were treated with the bleaching agents for 8 h/day during 14 days, while G4 and G8 were exposed to the bleaching agents for 30 min twice a day during 14 days. The enamel blocks were stained with 0.1 mM rhodamine B solution and the demineralization was quantified using fluorescence intensity detected by CLSM. Data were analyzed using ANOVA and Fisher's tests (α=0.05). For the SE groups, the bleaching treatments increased significantly the demineralization area when compared with the unbleached group. In the CL groups, no statistically significant difference was observed (p>0.05). The addition of ACP or Ca in the composition of the whitening products did not overcome the effects caused by bleaching treatments on SE and neither was able to promote remineralization of CL.
Keywords: Bovine enamel; Confocal laser scanning microscopy; Whitening; amorphous calcium phosphate; calcium phosphate; hydrogen peroxide; tooth bleaching agent; analysis of variance; animal; cattle; chemically induced disorder; confocal microscopy; dental caries; dental procedure; drug effect; enamel; hardness; methodology; pathophysiology; tooth disease; Analysis of Variance; Animals; Calcium Phosphates; Cattle; Dental Caries; Dental Enamel; Hardness; Hydrogen Peroxide; Microscopy, Confocal; Tooth Bleaching; Tooth Bleaching Agents; Tooth Demineralization; Tooth Remineralization